PROBLEMATIK IMPLEMENTASI PENGUATAN POTENSI SISWA DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Unisa, Lesni; Azzahra, Siti Fatimah; Juanda, Mayshir; Rahmanda, M Dino; Abdurrahmansya, Abdurrahmansya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The Independent Curriculum was designed as a strategic response to create flexible learning to optimize students' interests and talents. However, its implementation at the elementary school level still faces various complex obstacles that prevent students from maximizing their potential. This study aims to analyze the challenges of implementing this curriculum through a qualitative approach using a literature review method, which examines secondary data from various scientific literature and relevant documents. The research findings outline three fundamental obstacles. First, the limited availability of resources and technology-based learning media, which reduces the effectiveness of the knowledge transfer process. Second, the imbalance in school readiness, including disparities in facilities between urban and remote areas, and variations in teacher competency in adapting new pedagogical methods. Third, the lack of parental support and understanding of this educational paradigm, which leads to a lack of synergy between the learning environment at school and at home. Based on this analysis, it is concluded that the success of the Independent Curriculum does not depend solely on regulations but rather requires integrative collaboration between the government, schools, and parents to create a conducive educational ecosystem for the realization of independent and creative student profiles. ABSTRAKKurikulum Merdeka dirancang sebagai respons strategis untuk menciptakan pembelajaran yang fleksibel guna mengoptimalkan minat dan bakat peserta didik. Kendati demikian, implementasinya di tingkat sekolah dasar masih dihadapkan pada berbagai hambatan kompleks yang menghalangi penguatan potensi siswa secara maksimal. Penelitian ini bertujuan untuk menganalisis problematika penerapan kurikulum tersebut melalui pendekatan kualitatif dengan metode studi kepustakaan, yang mengkaji data sekunder dari berbagai literatur ilmiah dan dokumen relevan. Temuan penelitian menguraikan tiga kendala fundamental. Pertama, keterbatasan ketersediaan sumber daya dan media pembelajaran berbasis teknologi yang mengurangi efektivitas proses transfer ilmu. Kedua, ketimpangan kesiapan sekolah yang mencakup disparitas fasilitas antara wilayah perkotaan dan daerah terpencil, serta variasi kompetensi guru dalam mengadaptasi metode pedagogik baru. Ketiga, minimnya dukungan dan pemahaman orang tua terhadap paradigma pendidikan ini, yang menyebabkan kurangnya sinergi antara lingkungan belajar di sekolah dan di rumah. Berdasarkan analisis tersebut, disimpulkan bahwa keberhasilan Kurikulum Merdeka tidak hanya bergantung pada regulasi, melainkan menuntut kolaborasi integratif antara pemerintah, sekolah, dan wali murid untuk menciptakan ekosistem pendidikan yang kondusif demi terwujudnya profil pelajar yang mandiri dan kreatif.